2006
DOI: 10.1021/es060412t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intracellular Resuscitation of Legionella pneumophila in Acanthamoeba polyphage Cells on the Antimicrobial Properties of Silver and Copper

Abstract: The property of Legionella pneumophila entering into a viable but noncultivable (VBNC) state under drinking water conditions (50 mL, pH 7.0, and 25 degrees C) and the intracellular resuscitation in Acanthamoeba polyphage cells were investigated. Then, the survival profiles of L. pneumophila residing in the planktonic phase and the endosymbiosis phase against antimicrobial silver and copper reagents were differentially compared with the case of Pseudomonas aeruginosa. The number of L. pneumophila in a cultivabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 27 publications
3
32
0
1
Order By: Relevance
“…Similar studies have reported Burkholderia pseudomallei as being more resistant to monochloramine, chlorine and UV once it is protected in Acanthamoeba astronyxis trophozoites (Howard and Inglis 2005). A decreased efficacy of silver and copper was reported against Legionella pneumophila and Pseudomonas aeruginosa within Acanthamoeba polyphaga trophozoites (Hwang et al 2006). Growth in different amoebal hosts may also influence the biocide susceptibility of a particular bacterial strain; this was recently evidenced with L. pneumophila replicated from Hartmannella vermiformis which displayed greater resistance to chlorine than cells replicated from A. castellanii (Chang et al 2009).…”
Section: Pathogen Protection In Multispecies Biofilmssupporting
confidence: 58%
“…Similar studies have reported Burkholderia pseudomallei as being more resistant to monochloramine, chlorine and UV once it is protected in Acanthamoeba astronyxis trophozoites (Howard and Inglis 2005). A decreased efficacy of silver and copper was reported against Legionella pneumophila and Pseudomonas aeruginosa within Acanthamoeba polyphaga trophozoites (Hwang et al 2006). Growth in different amoebal hosts may also influence the biocide susceptibility of a particular bacterial strain; this was recently evidenced with L. pneumophila replicated from Hartmannella vermiformis which displayed greater resistance to chlorine than cells replicated from A. castellanii (Chang et al 2009).…”
Section: Pathogen Protection In Multispecies Biofilmssupporting
confidence: 58%
“…Still, Acanthamoeba spp. are frequently used to study proliferation and growth of L. pneumophila within freeliving protozoa and numbers between ÏŸ1.0 Ï« 10 2 and 4.5 Ï« 10 4 CFU of L. pneumophila per amoeba or vesicle have been reported (18,22,24,43,44). Growth of Acanthamoeba spp.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that unculturable L. pneumophila may resuscitate to a fully virulent form by passage through an amoebal host (30,33,34,36) and therefore provide a largely undetected source of infections. Unculturable Legionellae have been observed for example after prolonged incubation in laboratory tap water microcosms at different temperatures, including elevated temperature at 42°C (36), heat shock (50 -70°C) (37), following disinfection (31)(32)(33), and after treatment with heavy metals (38).…”
mentioning
confidence: 99%